Ecosystem restoration in India during the United Nations decade on ecosystem restoration: the way forward. Issue 5 (9th June 2022) - Singh, Kripal; Abhilash, Purushothaman C.; Maiti, Subodh Kumar; Venkataraman, Ramesh
Abstract : This article introduces the special section on "Ecosystem Restoration in India: Status Quo and the Way Forward to Achieve Land Degradation Neutrality" and provides an overview of the four papers that constitute this section.